1998
DOI: 10.1161/01.str.29.9.1882
|View full text |Cite
|
Sign up to set email alerts
|

The Apolipoprotein E ε4 Allele and Outcome in Cerebrovascular Disease

Abstract: Background and Purpose-Polymorphism of the apolipoprotein E gene (APOE) may influence outcome after traumatic brain injury and intracerebral hemorrhage, with the ⑀4 allele being associated with poorer prognosis. We investigated APOE allele distribution in acute stroke and the effect of the ⑀4 allele on outcome. Methods-APOE genotypes were determined in 714 stroke patients: 640 ischemic stroke and 74 intracerebral hemorrhage patients. The survival effect of the ⑀4 allele was assessed with the use of a stratifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 53 publications
(37 reference statements)
3
73
0
3
Order By: Relevance
“…However, several previous studies have shown no evidence of association between APOE4 and outcome in patients with ischemic stroke. 22,23 To explain the adverse prognostic effect of APOE4 on SAH patients, apolipoprotein E4 must act either indirectly or through a mechanism other than ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, several previous studies have shown no evidence of association between APOE4 and outcome in patients with ischemic stroke. 22,23 To explain the adverse prognostic effect of APOE4 on SAH patients, apolipoprotein E4 must act either indirectly or through a mechanism other than ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although not exclusively, it appears that proinflammatory and prothrombotic genes may play a significant role in the etiology and outcome after stroke in nonoperative settings. [5][6][7][8][9][10][11] Consequently, we hypothesized that specific genetic polymorphisms modulate the risk of in-hospital stroke following cardiac surgery.…”
mentioning
confidence: 99%
“…Second, it has been suggested that a combination of subclinical infection of the brain with HSV-1 and carriage of apoE ε4 may act in concert to predispose to Alzheimer's disease (13). Third, there is accumulating evidence that apoE ε4 is associated with poor outcome after several forms of acute brain injury, including damage caused by trauma (7) and intracerebral hemorrhage (21). Furthermore, binding of HSV-1 to the various subclasses of serum lipoproteins has been described, including the interaction of purified glycoprotein B from HSV-1 with ApoE (10).…”
mentioning
confidence: 99%